A história secreta do Século XX: metaficção e quadrinhos em Planetary - Santos Filho, Márcio Moreira dos (2019)
The present work disserts about Planetary, an American comic by Warren Ellis and John Cassaday that relates the explorations of the organization of the same name in search of the secret history of the 20th century. But this history is nothing more than the historiography of pop culture in the century. The work uses "archeology of the impossible" as a metaphor to incorporate intertexts of Victorian literature, pulp magazines, cinema, and comics to construct a quasi-erudite survey of the inner workings and influences of the superhero genre. Planetary is a metafiction, narrative that systematically draws attention to itself as an artifact, revealing its intertexts as the product of historical articulations. The present research intends to study the metafiction in the comic books from Planetary, examining how the literary concept works when applied to the comics language, taking into account the materiality of the medium. For this, we structure the work in two distinct parts, after surveying the state of the art on the object. In the first part, which comprises chapters two and three, we dedicate ourselves to form. We review the concept of metafiction according to Waugh (1984), Hutcheon (1989) and Currie (1995), and review the metacomic proposed by Jones (2005), Gonzalez (2014) and Cook (2017). Then, we discuss the conditions for metafictionality in comics, starting from questions about enunciation (CHUTE, 2008; GARCIA, 2014; HATFIELD, 2005), the materiality of the image (LAMBEENS; PINT, 2015, CARNEIRO, 2015) and the possibility of aesthetic illusion (GOMBRICH, 1984; WOLF, 2013). In the second part, we analyze four constitutive aspects of the comic from the perspective of its intertextual (GENNETE, 1989; SANDERS, 2006) and interpictoric strategies (DIDI-HUBERMAN, 2009; ISEKENMEIER, 2013): the covers, the frames, the characterizations and the style of drawing. From there, we try to interpret the game of imitation and transformation that the Planetary uses to make its political comments on power and culture.